Investigation of carbonyls in cloudwater during ICARTT - Li, Shao-Meng; Macdonald, Anne Marie; Leithead, Amy; Leaitch, W. Richard; Gong, Wanmin; Anlauf, Kurt G.; Toom-Sauntry, Desiree; Hayden, Kathy; Bottenheim, Jan; Wang, Daniel (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 2008)
Air borne measurements carried out in the summer of 2004 in the lower Great Lakes region as part of the ICARTT 2004 study are used to examine the effects of clouds on the carbonyls in the atmosphere. Concentrations of seven carbonyl species in bulk cloudwater samples were measured with concurrent gas phase HCHO measurements. In the cloudwater, the most abundant carbonyl was HCHO with a median value of 11.9 mu mol L-1, followed by acetaldehyde (4.3 mu mol L-1), acetone (1.9 mu mol L-1), pentanal (1.4 mu mol L-1), benzaldehyde (0.5 mu mol L-1), butanal (0.4 mu mol L-1), and propanal (0.2 mu mol L-1). The relative abundance of propanal to acetaldehyde in the cloudwater was substantially lower than estimates from primary emissions. The cloudwater abundance of HCHO relative to the sum of the other carbonyls was found to increase with altitude in the clouds that penetrated the boundary layer. During most flights, the total in-cloud HCHOt (cloudwater + interstitial gas phase) was similar to cloud base HCHOg, suggesting that HCHO was distributed between the two phases through partitioning governed by Henry's law. However, during at least one flight, HCHOt was significantly depleted in the cloud. Finally, the equilibrium gas phase mixing ratios predicted from the cloudwater for all carbonyls but HCHO were much higher than previously measured in the gas phase.